SENTINEL LYMPH NODE IN MALIGNANT MELANOMA-COMPARISON OF PLANAR LYMPHOSCINTIGRAPHY AND SPECT/CT - Sunil Nair A; Göbet G; Vargas Jimenéz E; Jankulovska A; Manevska N; Makazlieva T; Jovanovski-Srceva M; Stojanoski S (MIT Univerzitet Skopje, 2023)
Introduction: Sentinel lymph node (SLN) biopsy is a minimally invasive alternative to systematic lymphadenectomy for assessment of nodal status in oncologic surgery. The objective of our study was to evaluate the results obtained from planar lymphoscintigraphy and SPECT/CT for preoperative localization of the SLN in melanoma patients. Materials and Methods: Retrospective analysis of 48 nuclear medicine images (24 planar lymphoscintigraphy images and 24 SPECT/CT) in 24 patients with malignant melanoma was performed. All patients underwent planar lymphoscintigraphy and SPECT/CT after peritumoral/around the scar application of 4 mCi 99mTc-SENTI-SCINT on the day of surgery. Descriptive statistics, Wilcoxon Matched Pairs Test and Spearman rank R coefficient were used for data analyses. Results: 24 patients (14 males, 12 females) with mean age at diagnosis of 51.08 ± 12.21 years were included in the study. Melanomas were most frequently located in the trunk with the left axillary region being the most common SLN location. In one patient (4%) SLN was not detected on planar lymphoscintigraphy, while the detection rate of SPECT/CT was 100%. Average number of detected SLN was 1.57 ± 0.85 and 2.11 ± 1.4 on planar lymphoscintigraphy and SPECT/CT respectively. SPECT/CT showed 14 SLNs more than PL and revealed additional lymphatic drainage regions in 8 patients. We found a statistically significant difference in the number of detected SLNs on planar lymphoscintigraphy and SPECT/CT ( p= <0.05). Conclusion: Planar lymphoscintigraphy is the method of choice for SLN identification providing a high detection rate. However, SPECT/CT should be used as an additional diagnostic tool to PL for precise anatomical location, detection of additional SLNs and reduction of falsepositive and false-negative rate.